Assessing Senior High Student’s Learning Experiences in Mathematics - Casinillo, Leomarich Fortugaliza; Palen, May Ann E.; Casinillo, Emily L.; Batidor, Paulo G. (Universitas Negeri Makassar, 2020)
In this study, the learning experience and its cognitive factors of Mathematics among senior high school students of Visayas State University were investigated using a correlational research approach. Â A complete enumeration of 222 grade 11 and 12 senior high students in the second semester of school year 2018-2019 were used as the participants of the survey. Using a developed structured questionnaire, a primary data was employed. Results showed that the mathematics attitude of students influence their learning experience and academic performance. Mathematics anxiety has a negative effect on the students learning experience especially for females. However, mathematical resilience locates itself in a positive psychology which addresses mental wellness and makes the students positively perceived that mathematics is interesting even if it is challenging. Â Also, results revealed that senior high school students are mostly visual learners in mathematics, which implies that students practice visualizing or pictures numbers/equations and other concepts in their mind. Furthermore, it can be gleaned that an academic performance is not just derived from study habits but to their motivation and interest in mathematics